Conference lanyards; why does it take so long to provide health hazard free options? - Matthew Carvey; Robert Hage (Elsevier, 2021)
Purpose: With a relatively simple object such as a lanyard holding an ID badge the translational phenomenon of why it takes so long for inventions or knowledge to reach consumers or beneficiaries is investigated. Basic procedures: Two collections of ID badges with and without lanyards were obtained and categorized according to the type of conference or institution and the type of possible harm the user of the ID badge may be exposed to. Findings: Lanyards were investigated for the material they were made of, the manner in which they were attached to the ID badge and the type of possible harm they could cause. Of the four types of possible harm, Harmful (H), Harmful by Individual Choice (HIC), Not Harmful (NH) and Safe (S), only 16% can be considered safe because of breakaway latches provided. Harmful but by individual choice because of the addition of an alternative method, a safety pin, for attaching the ID badge was found in 15% of the samples. The safest method was only a safety pin or magnet for displaying the ID badge. Over a two-decade period, there was no sign of a trend to more safety regarding the display of the ID badge. Conclusions: Safety breakaway latches or other means of preventing harm when wearing an ID badge are not commonly supplied at conferences. The safety issue of lanyards worn around the neck at conferences has not shown improvement over the years. The manufacture of lanyards of a non-durable material that will tear when force is applied is a suggested option. Lanyards should have a minimum of three breakaway latches.